2022
DOI: 10.3390/pr10030514
|View full text |Cite
|
Sign up to set email alerts
|

Heat Pump Drying of Kelp (Laminaria japonica): Drying Kinetics and Thermodynamic Properties

Abstract: The main objective of this research is the study of the drying kinetics and thermodynamic properties of kelp using heat pump drying technology. The effects of the independent variables of temperature (20–50 °C), air velocity (0.3–1.3 m/s), humidity (20–50%), and thickness (0.8–4.2 mm) on the drying time, moisture uniformity, effective moisture diffusivity (Deff), activation energy (Ea), enthalpy (ΔH), entropy (ΔS), and Gibbs free energy (ΔG) were investigated. The results show that the Page model was effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…This may be due to the rapid evaporation on the surface of kelp, which makes it difficult to form a stable water concentration difference between the surface and the interior of kelp [ 26 ]. The results were consistent with the pattern observed by Zhang et al [ 9 ] in the HP for small-sized kelp slices, though the drying time of the proposed SHPD was shortened by 2–7 h. In addition, when the temperature was 40−50 °C, the drying time of HP was 33% longer than that of S−HP, and the average drying rate was 7.3% lower, indicating that solar irradiation could significantly improve the drying rate of kelp.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…This may be due to the rapid evaporation on the surface of kelp, which makes it difficult to form a stable water concentration difference between the surface and the interior of kelp [ 26 ]. The results were consistent with the pattern observed by Zhang et al [ 9 ] in the HP for small-sized kelp slices, though the drying time of the proposed SHPD was shortened by 2–7 h. In addition, when the temperature was 40−50 °C, the drying time of HP was 33% longer than that of S−HP, and the average drying rate was 7.3% lower, indicating that solar irradiation could significantly improve the drying rate of kelp.…”
Section: Resultssupporting
confidence: 93%
“…This indicated that the Page model could describe the drying kinetics of kelp more accurately. In a previous study on the HP for small-sized kelp slices, the Page model also demonstrated effective fitting to the variations in MRs [ 9 ], but Samimi et al [ 27 ] and Roa et al [ 28 ] found that the Aghbashlo model and the Midilli−Kucuk model were better in describing solar hot air drying of tomato slices and in solar drying of cherries.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HPD recycles the sensible and latent heat in the exhaust gas during drying, reducing energy consumption. It is the most suitable new environmental-friendly and energy-saving drying method to replace traditional drying at this stage and has been employed in the drying of kelp (Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%